THE ANALYSIS OF EFFECT OF GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY AND LEVERAGE ON FINANCIAL SERVICES COMPANYPROPERTY AND REAL ESTATE THAT REGISTERED IN THE SECURITY EXCHANGE INDONESIA YEAR 2012-2016 - Simarmata, Asianna Martini (International Journal of Public Budgeting, Accounting and Finance, 2018)
The purpose of this research is to knowing and analyzing the influence of Good Corporate Governance (in terms of independent commissioners, managerial ownership, institutional ownership and audit committee), Corporate Social Responsibility ( in terms of education, health, social and environmental ) and leverage ( in terms of debt to asset ratio and debt to equity ratio )on the financial performance of service companies in the Property and Real Estate sub-sectors listed on the IDX for the 2012-2016 period. This type of research is hypothesis testing or explanatory research . The population in this study are companies in the Property and Real Estate sub-sector service companies listed on the IDX for the period 2012-2016 as many as 49 companies. The selection of research samples is based on a purposive sampling method and obtained a sample of 24 companies . The data used in this study are secondary data, namely quantitative data obtained from the Indonesia stock exchange site (www.idx.co.id) and data collection is done by downloading the financial statements of the Property and Real Estate sub-sector service companies . The results of this study prove that (1) independent board of directors and managerial ownership have a positive but not significant effect on financial performance while institutional ownership and audit ownership have a positive and significant effect on the financial performance of service companies in the Property and Real Estate sub-sectors listed on the IDX. for the period of 2012-2016 , (2) health CSR has a significant positive effect on financial performance, social CSR has a positive but insignificant effect on the company's financial performance while the environmental education and CSR has a negative and significant effect on the financial performance of service companies Real Estate and Property sub-sectors IDX lists are in the period 2012-2016, and (3) DAR has a negative and insignificant effect on the company's financial performance while DER has a negative and significant effect on the financial performance of service companies in the Property and Real Estate sub-sectors listed on the IDX for the period 2012-2016.